Knowledge, Attitude and Practice among Postnatal Mothers Regarding Postnatal Exercise in Selected Villages at Pooncheri, Kanchipuram District,Tamil Nadu, India (Medico Legal Update, 2020)
A descriptive study to assess the knowledge, attitude and practice among postnatal mothers regardingpostnatal exercise in selected village adopted by rural health centrepooncheri, Kanchipuram District, TamilNadu, India. The objectives are to assess the knowledge, practice and attitude among postnatal mothersregarding postnatal exercise in selected villages adopted by rural health centrepooncheri, KanchipuramDistrict, Tamil Nadu, India . To find out the association between level of knowledge, practice and attitudewith demographic variables. The purposive sampling technique was used and the samples were 73. The datacollection tools were validated and reability was established. The data were collected by self-administeredquestionnaire. The collected data tabulated and analyzed. Descriptive and inferential statistics were used.The study shows, In knowledge, 12.3% of the mothers had adequate knowledge, 52% of mothers hadmoderate knowledge and 35.6% of mothers had inadequate knowledge. In practice, 1.3% of mothers hadadequate practice, 38.3% of mothers had moderate practice and 60.2% of mothers had inadequate practice,In attitude, 60.2% of mothers had negative attitude, 39.7% of mothers had undecided attitude and none ofmothers had positive attitude among postnatal exercise.